2011
DOI: 10.1039/c1cy00214g
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate addition of arylboronic acids to α,β-unsaturated carbonyl compounds in aqueous medium using Pd(ii) complexes with dihydroxy-2,2′-bipyridine ligands: homogeneous or heterogeneous nano-catalysis?

Abstract: The conjugate addition of arylboronic acids to a,b-unsaturated carbonyl compounds in water under air has been studied using a series of palladium(II) derivatives containing symmetrically disubstituted-2,2 0 -bipyridine ligands. Among them, best results were obtained with complex [PdCl 2 {3,3 0 -(OH) 2 -2,2 0 -bipy}] (2a), which selectively provides the desired addition products in good to high yields under mild conditions. Catalytically active palladium nanoparticles are formed in the course of the reactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…Transmission electron microscopy (TEM) studies performed on the reaction mixtures obtained after the catalytic runs indicated the formation of palladium nanoparticles (Pd‐NPs) under pulsed US activation in glycerol. Pd‐NPs formation under similar conditions has recently been attributed to the reducing character of glycerol,31 however, as previously mentioned, boronic acids can be also responsible for Pd(II) reduction 33,34. In our case, we observed a different average size depending on catalyst/substrate combination (Figure 4).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Transmission electron microscopy (TEM) studies performed on the reaction mixtures obtained after the catalytic runs indicated the formation of palladium nanoparticles (Pd‐NPs) under pulsed US activation in glycerol. Pd‐NPs formation under similar conditions has recently been attributed to the reducing character of glycerol,31 however, as previously mentioned, boronic acids can be also responsible for Pd(II) reduction 33,34. In our case, we observed a different average size depending on catalyst/substrate combination (Figure 4).…”
Section: Resultssupporting
confidence: 81%
“…The solubility test of catalysts 1 – 4 in glycerol revealed that the sulfonate‐derived catalysts 3 and 4 are completely soluble, while catalysts 1 and 2 were only sparingly soluble (see Figure S1 of the Supporting Information). The catalytic activity observed in glycerol could be attributed to the formation of nanoparticles formed most probably by the polyol method31,32 or by reduction of Pd(II) to Pd(0) by action of the boronic acids employed33,34 (Figure 3). Stabilized by the ligands and/or by the solvent (glycerol), the nanoparticles remained small in size and did not agglomerate.…”
Section: Resultsmentioning
confidence: 99%
“…Similar phenomenon was reported by Cadierno and coworkers. 12 They investigated palladium and bipyridine catalysts in the reaction of arylboronic acids with unsaturated carbonyl compounds in aqueous medium. Under strongly basic conditions, the catalyst solubility increased and aqueous nano-dispersed solutions could be prepared, but extensive aggregation was observed Scheme 1 Main products in butanol and ethanol condensation.…”
Section: Catalyst Development From Butanol Condensationmentioning
confidence: 99%
“…Although lowering the reaction temperature to 50 °C did not alter the diastereoselective ratio (entry 12 vs entry 13), the conversion deteriorated significantly even if the reaction proceeded for 18 h. Other ligands such as 4,4′-dinitro-2,2′-bipyridine, [2,2′-bipyridine]-3,3′-diol, 1,10-phenanthroline, 2,9-dimethyl-1,10-phenanthroline, and 6,6′-dimethyl-2,2′-bipyridine (entries 15–20) were also screened, and all afforded the product in a poor diastereoselective ratio. Phosphorus ligands such as PPh 3 , PCy 3 , S-phos, and X-phos did not work in this reaction.…”
Section: Resultsmentioning
confidence: 99%